GENDER ANALYSIS IN CONSTRUCTION PROJECT - Retno Indryani; Yusroniya Eka Putri Rachman Waliulu; Dayat Indri Yuliastuti (Journal of Civil Engineering, 2010)
Construction project staff is domminated by men. Otherwise, the percentage of woman in education the field of construction, such as Civil Engineering and Architecture is growing. The purpose of this paper is to analize gender aspect in construction project. The method used is survey to men and women respondens that work on construction company in Surabaya. Gender aspect analized is the opportunity to participate female, the male and female ratio capability and the obstacle of woman carier in construction project. The results show that women participation is less than men. Men and women have the same ability in several areas. There are several obstacles that are often experienced by women in construction projects, including the barriers of discrimination.